Improving Quality of Care on Patient Satisfaction in Health Service Facilities by Rating on Google Maps: Literature Review - Permatasari, Putri; Rajebta, Nikita Alia (Care : Jurnal Ilmiah Ilmu Kesehatan, 2025)
Quality health services are services that are provided effectively and efficiently, tailored to the needs and expectations of patients, but still in accordance with existing codes of ethics and standards, thus enabling the achievement of optimal levels of health.  Health service institutions for the community, where every health facilities are required to always improve the quality of service in order to achieve the highest level of health. Every patient who has received service can provide their opinion through the Google Maps comments section which can describe the quality of service of the health facilities. The method used in this article is a literature review and the search for articles is carried out through 2 online databases: Google Scholar for national journals and PubMed for international journals. According to the reviewed literature, the rating given by health facility visitors affects the quality of the health facility. This is due to dissatisfaction with the health services received in the form of reviews with narratives describing feelings of annoyance, anger, and disappointment. Ratings on Google Maps provides real-time information about the quality of service at a health facility based on patient reviews.